Horizontal transport and seasonal distribution of nutrients, dissolved oxygen and chlorophyll-a in the Gulf of Nicoya, Costa Rica: a tropical estuary - Kressa, Nurit (2002)
The distributions of salinity, temperature, nutrients, dissolved oxygen and chlorophyll-a (chl-a) concentrations in the Gulf of Nicoya, Costa Rica, during the rainy and dry seasons are presented. In the rainy season, the entire Gulf is strongly stratified due to high riverine discharge; surface temperature decreases and salinity increases towards the sea and most of the Gulf is undersaturated with dissolved oxygen. In the dry season, the Gulf is still stratified although without the strong fresh water signal identified in the rainy season. The lowest surface temperatures appear in the middle of the Gulf whilst the salinity generally decreases towards the upper Gulf. Only the deep waters (below 30 m depth) are undersaturated with dissolved oxygen. In the lower Gulf, oversaturation reaches up to 134% at the surface. The concentration of Si(OH)4 in the Gulf is much higher during the rainy season than in the dry season, whilst PO4 is not seasonally dependent. Surficial concentrations of NO3+NO2 in the upper Gulf are higher in the dry season than in the rainy season; whilst in most of the lower Gulf, the concentrations are lower in the dry season. Surficial chl-a concentrations in the Gulf are higher in the rainy season, in particular, close to the Tarcoles outflow. A three-component mixing diagram describes the spatial distribution of the nutrients, during both seasons. Riverine waters from the Tempisque (high nutrients and low salinity) are mixed with surface waters from the lower Gulf (higher salinity and lower nutrients). The resulting water then mixes with oceanic water. Salinity in relation to PO4 is seasonally dependent in the upper Gulf; the riverine end member during the dry season is higher, by a factor of 4, than during the rainy season. There is a significant correlation between NO3+NO2 and salinity only during the dry season in the upper Gulf; this is probably a result of phytoplankton consumption of N, in the rainy season. The calculated NO3+NO2 riverine end member in the rainy season was 3.4 times lower than in the dry season, which is similar to that found for PO4, indicating anthropogenic sources of N and P. The Si(OH)4 riverine end member is higher in the rainy season; this is a result of natural rock weathering and increased transport, due to higher riverine discharge. The productivity in the Gulf of Nicoya is potentially limited by the availability of nitrogen, probably as the direct consequence of the introduction of riverine waters with high phosphorus concentration (low N/P ratios). Si(OH)4 is always in great stoichiometric excess over N and P. r 2002 Elsevier Science Ltd. All rights reserved